Sharing Financial Literacy of Malaysian Students Through Lessons Learned from Indonesian Students - Waluyo, Dwi Eko; Wulandari, Respati; Astuti, Sih Darmi; Sasongko, Teguh Haryo; Banu, Azlina (Research Collaboration Community (Rescollacom), 2025)
Financial literacy equips university students with the knowledge they need to navigate their finances as they grow into independent adults. Our outreach to Malaysian students had two goals: to strengthen their financial understanding and to gauge their current literacy levels. We achieved this through classroom presentations to the students, Q&A sessions, and discussions with student‑affairs staff at Malaysian universities. The core material delivered in the financial literacy session focused on sources of funding for making investments. The findings suggest that Malaysian students deal with challenges much like those faced by Indonesian students, especially in developing essential financial management skills, as their parents entrust them with the responsibility of managing their living and educational expenses independently. Malaysian students also demonstrate the same awareness as their Indonesian peers regarding the importance of engaging in entrepreneurial activities, which help prepare them to become successful economic contributors. The material presented was highly relevant for students interested in becoming entrepreneurs.